Neural nano-optics for high-quality thin lens imaging - Ethan Tseng (Nature Portfolio, 2021)
While meta-optics have the potential to dramatically miniaturize camera technology, the quality of the captured images remains poor. Co-designing a single meta-optic and software correction, here the authors report on full-color imaging with quality comparable to commercial cameras.